Plastics piping systems for non-pressure underground drainage and sewerage. Unplasticized poly(vinyl chloride) (PVC-U), polypropylene (PP) and polyethylene (PE). Specifications for ancillary fittings and shallow chambers Part 1, (10th July 2020) - British Standards Institution,
No abstract available